Dual functional star polymers for lubricants. Issue 89 (12th September 2016) - Cosimbescu, Lelia; Robinson, Joshua W.; Zhou, Yan; Qu, Jun
Abstract : Star-shaped poly(alkyl methacrylate)s (PAMAs) with a 3-arm architecture were designed, prepared and their performance as a dual additive (viscosity index improver and friction modifier) for engine oils was evaluated. Abstract : Star-shaped poly(alkyl methacrylate)s (PAMAs) with a three arm architecture were designed, prepared and their performance as a dual additive (viscosity index improver and friction modifier) for engine oils was evaluated. Furthermore, the structure–property relationships between the macromolecular structure and lubricant performance were studied, such as molecular weight and polarity effects on the viscosity index. Several co-polymers of dodecylmethacrylate with polar methacrylates in various amounts and various topologies, were synthesized as model compounds. Star polymers with a polar content of at least 10% in a block or tapered block topology effectively reduced the friction coefficient in both mixed and boundary lubrication regimes. However, a polar content of 20% was efficient in reducing friction in both random and block topologies.